Esketamin modulira postoperativne biohemijske markere oksidativnog stresa, upale i imunološke disregulacije u laparoskopskoj hirurgiji kolorektalnog karcinoma: Esketamine Alters Biochemical and Immune Markers in Colorectal Surgery - Chen, Peng; Qian, Kun; Zhu, Kairun; Lu, Xiaoqing; Liu, Dajin (Journal of Medical Biochemistry, 2025)
Background: Laparoscopic colorectal cancer surgery, while minimally invasive, induces systemic oxidative stress, inflammation, and immune dysfunction through surgical trauma and anesthesia-related stress. Esketamine, an NMDA receptor antagonist with antioxidant and anti-inflammatory properties, may mitigate these biochemical perturbations. This study evaluated esketamine’s effects on serum biomarkers of oxidative stress (glutathione, catalase, malondialdehyde, superoxide dismutase), inflammatory mediators (TNF-α, CRP, IL-6), and T lymphocyte subsets in patients undergoing laparoscopic colorectal cancer resection. Methods: In this randomized controlled trial, 150 stage I-II colorectal cancer patients were allocated to esketamine (0.25 mg/kg bolus + 0.12 mg/kg/h infusion) or control (saline) groups during standardized anesthesia. Pre- and postoperative serum levels of oxidative stress markers (GSH, CAT, MDA, SOD), inflammatory cytokines (TNF-α, CRP, IL-6), and immune cell subsets (CD3+, CD4+, CD8+, CD4+/CD8+ ratio) were quantified via ELISA and flow cytometry. Statistical analysis compared intergroup differences using t-tests and chi-square tests. Results: Postoperatively, the esketamine group exhibited significantly attenuated oxidative stress, with higher GSH (72.43 ± 6.63 vs. 60.16 ± 5.57 mg/mL, P < 0.05), CAT (92.56 ± 8.31 vs. 82.81 ± 7.75 U/mL), and SOD (84.53 ± 8.02 vs. 69.93 ± 7.05 nU/mL), alongside lower MDA (6.41 ± 0.52 vs. 9.52 ± 0.63 mmol/L). Pro-inflammatory cytokines were reduced (TNF-α: 40.32 ± 4.84 vs. 54.37 ± 5.80 pg/mL; IL-6: 50.83 ± 5.05 vs. 82.38 ± 8.46 pg/mL, P < 0.05). Immune function preservation was evident through elevated CD3+ (45.18 ± 5.01% vs. 37.05 ± 4.92%) and CD4+ T cells (26.51 ± 2.76% vs. 19.78 ± 2.09%), with a balanced CD4+/CD8+ ratio (1.12 ± 0.12 vs. 0.72 ± 0.09). Conclusion: Esketamine-based anesthesia significantly ameliorates postoperative oxidative damage, suppresses inflammatory cytokine release, and preserves cellular immune homeostasis, as evidenced by targeted biochemical and immunological analyses. These findings highlight esketamine’s role in modulating perioperative biochemical pathways, potentially enhancing recovery in colorectal cancer surgery.